An Untenable Dichotomy: The Idea of Home in John Okada’s No-No Boy - Li, Stony Brook University, USA, Wenxin (Asiatic: IIUM Journal of English Language and Literature, 2015)
Given the particular history of Asian immigration in the U.S., the idea of a stable and safe home has been regularly sought after in Asian American literature. Whether these Asian immigrants abandoned their homeland due to war, famine, or other disasters, the urgency to find safety and protection in a new home in America remains one of most enduring themes. In No-No Boy, a 1957 novel by John Okada that explores the traumatic aftermath of the internment of Japanese Americans during and after World War II, the idea of home is presented in an unstable dichotomy between affirming Americanness and perpetual foreignness. The novel's protagonist Ichiro Yamada regains his freedom after serving a prison term for refusing to join the American military in the war against Japan, only to find a dysfunctional home in the back of the family grocery store. Everything here is Japanese: the food, language and allegiance. Ichiro's home is contrasted with Kenji's home, which showcases its Americanisation in every aspect. By setting up this dichotomy, Okada exposes the tension within the Japanese American community in the difficult process of assimilation into American society. The ultimate hope for Ichiro seems to lie in a home that is yet to be built, a life with Emi in an America that simply accepts him for who he is without racialisation.